Химическое состояние атомов углерода в продуктах детонационного синтеза алмаза до и после химической обработки - Дементьев, А.П.; Маслаков, К.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
Definition of a chemical condition of atoms of carbon in nanodiamond particles, especially on their surfaces, is obviously necessary for understanding of the mechanism of formation of nanodiamond particles, and also for earning out of various reactions on purpose offunctionalization to their surface.